Abundance, Diversity and Distribution of Phytoplankton in Coastal Water Adjacent to St. Martin’s Island, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The purpose of this study was to ascertain the composition, abundance, and distribution of phytoplankton in the coastal waters of the Bay of Bengal, Bangladesh (BoB) adjacent to the St. Martin’s Island.Samples were collected from 14 stations on low tide during the day time from March 13 - 19, 2020. In the present investigation, a total of 62 diatoms and 6 dinoflagellates were identified. Among diatoms, most dominant species were contributed by the genera Coscinodiscus followed by Chaetoceros, Thalassiosira, and Thalassionema. Among dinoflagellates, four species of Ceratiumand one species from each of Dinophysisand Gonyaulax were identified. The cell count of total phytoplankton varied from 87,500-437,500 in d/m3 of sea water and the highest phytoplankton was found at station 4. Coscinodiscus was the most dominant genus of the centric diatoms in all the stations and its abundance ranged from 25,000-100,000 in d/m3. The highest number of Coscinodiscus was found at station 4. The result of this study showed that phytoplankton composition and their abundance varied from one station to another. But not much difference was observed among the ranges of physicochemical factors. Water temperature, salinity, pH and dissolved oxygen ranged from 26.5-27.17°C, 32.09-33.76 ppt, 8.16-8.20, and 5.85-6.12 mg/l, respectively. The species richness factor and the diversity index factor as determined with the help of generic abundance which revealed the ranges from 1.51-4.93 and 1.52-2.22, respectively. The ranges of salinity and temperature recorded in the present investigation are quite consistent with the optimum ranges reported for marine habitats. The qualitative structure of phytoplankton shows similarities with other studies carried out in the BoB at different times. However, variability in the population density of phytoplankton in different studied stations may not be responsible for different water quality parameters rather than oceanic currents and tides.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 21-34